Computer-Aided Planning and 3D-Printed Surgical Guide in Patients with Extreme Cubitus Varus Deformity: A Report of 2 Cases. Issue 4 (7th October 2022) - Marinelli, Alessandro; Guerra, Enrico; Rotini, Roberto; Mortellaro, Marco; Minopoli, Paolo; Pietroluongo, Livia Renata; Russo, Raffaele
Abstract : Case: We describe 2 patients with extreme triplanar cubitus varus deformity, treated with step-cut corrective virtually planned osteotomies and performed with custom-made surgical guides. The surgery was simulated on the patients' bone 3D-printed model to verify the effectiveness of the surgical plans. At a medium 21-month follow-up after surgery, in both patients, clinical and radiological results were fully satisfactory, and no complications have been reported. Conclusion: The precision of computer-aided surgical planning and custom-made surgical guides allow to perform reproducible and relatively safe surgeries even in extreme deformities where the surgical complexity could discourage attempts at surgical correction.